Thermal Decomposition Kinetics of Humic Substances Extracted from Mid-Rio Negro (Amazon Basin) Soil Samples - de Oliveira, Luciana Camargo [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Rosa, Andre Henrique [UNESP]; Botero, Wander Gustavo [UNESP]; Rocha, Julio Cesar [UNESP]; Cruz Romao, Luciane Pimenta; dos Santos, Ademir [UNESP] (Soc Brasileira Quimica, 2009)
In this work humic substances (HS) extracted from non-flooded (Araca) and flooded (Iara) soils were characterized through the calculation of stability and activation energies associated with the dehydration and thermal decomposition of HS using TGA and DTA, electronic paramagnetic resonance and C/H, C/N and C/O atomic ratios. For HS extracted from flooded soils, there was evidence for the influence of humidity on the organic matter humification process. Observations of thermal behaviour, with elemental analysis, indicated the presence of fossilized organic carbon within clay particles, which only decomposed above 800 C. This characteristic could explain the different thermal stability and pyrolysis activation energies for Iara HS compared to Araca HS.
Keywords: soils; humic substances; kinetics; thermal analysis; Amazon